Religious and Socio-Cultural Influences on DignityUSA Chapters - Voyles, Michelle (East Carolina University, 2023)
People who identify as both LGBTQ and Catholic have struggled with reconciling these identities as the larger Catholic church is anti-LGBTQ. There is little research on positive relationships between LGBTQ and Catholicism because most studies point out barriers between the two. This research will focus on a group that works to retain and bridge religious and sexual identities through social activism. DignityUSA is an activist group that primarily works for change in the larger Catholic church regarding its stance on the LGBTQ community. Founded in 1969 in Los Angeles, California by Father Patrick X. Nirdof, DignityUSA was originally a ministry that offered support and acceptance to those who identify as both Catholic and LGBTQ. LGBTQ Catholics often had a hard time merging their conflicting identities, so this ministry aimed at reliving their guilt and offering a safe space for them to be who they are. While DignityUSA started as a single ministry offering refuge to local community members, its presence became known nationally and other chapters began to open with the same mission. DignityUSA’s presence alone was an attempt at activism because it allowed people to not surrender their same-sex identities to be Catholic, which directly goes against Catholic beliefs, and nationally, various anointed priests, brothers, seminarians, and other leaders of the Catholic church were supportive of DignityUSA. There has been a large fluctuation in the number of DignityUSA chapters, with the general trend being a sharp increase, hitting a maximum number of chapters, then a sharp decrease. This research serves to analyze the fluctuations in the number of DignityUSA chapters per state and the years 1973-2009. This will be done through qualitative analyses of several independent variables’ impact on the number of DignityUSA chapters, including the number of social movement organizations, the number of Catholic Universities, the general religious and Catholic adherence, and the social and government ideology. By using multivariate analyses, I hope to identify correlations to help explain the fluctuation in chapters of this social movement organization.
Keywords: LGBTQ; Catholic; Statistics